Evidence-Based Behavior Management Strategies for Students With or at Risk of EBD: A Mega Review of the Literature. (August 2022) - Riden, Benjamin S.; Kumm, Skip; Maggin, Daniel M.
Evidence-based practices (EBPs) are strategies shown through rigorous experimentation to be effective when implemented as designed by educators in the field. The purpose of this review is to (a) describe the state and quality of evidence-based reviews and meta-analyses of studies on classroom and behavior management interventions for students with emotional and behavioral disorders (EBDs) and (b) summarize practices that can be deemed evidence-based. We identified 50 meta-analytic or systematic reviews encompassing 20 interventions implemented solely or in part with students with EBD. In total, our review identified eight interventions classified as EBPs for supporting students labeled with EBD in the meta-analytic literature. Implications for future research are presented.